Solution structure of a DNA hairpin and its disulfide cross-linked analog. - Cain, R J (1995)
The solution structures of a 21 base long DNA hairpin derived from the ColE1 cruciform, and an analog possessing a disulfide cross-link bridging the terminal bases, have been determined by NMR spectroscopy. The 8 bp long stem of these sequences adopts a B-form helix whereas the five base long single-stranded loop appears to be flexible and cannot be represented by a unique static conformation. NOESY cross-peak volumes, proton and phosphorus chemical shifts, and both homo- and heteronuclear coupling constants for the cross-linked hairpin are virtually identical to those measured for the unmodified sequence, even for the residues that are proximal to the cross-link. These results indicate that both hairpins are structurally isomorphous. Because this cross-link can be incorporated site specifically in a sequence independent manner, and does not appear to alter native conformation, it should prove broadly applicable in studies of DNA structure and function.